Alan Simpson's Windows XP Bible, Second Edition - Simpson, Alan (Wiley Publishing, 2011)
Comprehensive in its treatment of Microsoft's latest and greatest operating system for the masses, Alan Simpson's Windows XP Bible has an answer to most "How do I..." questions that are likely to arise in the minds of Windows XP users, particularly those who aren't too familiar with recent versions of Windows. If you're going to buy a Windows XP reference book for your office, this would be a good choice. The author--the respected Alan Simpson, who's put out similarly comprehensive books before--must have incredible patience, because he manages to document almost every Windows procedure down to the last option and the final "OK" click. Most people won't need this level of handholding--almost everyone has gained knowledge of the basic Windows conventions by now--and perhaps this book could have been more compact (as it is, it's pretty hefty) or contained more obscure details without it. But don't accuse Simpson of neglecting details.